SWISS – INDONESIA COOPERATION THROUGH “WISATA II” TO ENCOURAGE SUSTAINABLE TOURISM IN INDONESIA - Dwi Risma Novianti (Mediasi: Journal of International Relations, 2021)
The aim of this research is to know the cooperation of Swiss and Indonesia to encourage the realization of sustainable tourism through “WISATA II” project. The method used in this research is qualitative method by analyzing using foreign aid concept and sustainable tourism concept. The results of this study show that to encourage sustainable tourism in Indonesia, Swiss provides foreign aid in the form of grants and technical assistance. Swiss and Indonesian parties then cooperated to realize sustainable tourism by pay attention to 3 aspects. Environmental aspect through the realization of Solid Waste Management and Plastic Reduction Initiative. Economic aspects with marketing and local business development. As well as socio-cultural aspect with the concept of community based tourism. The influence of “WISATA II” in project destinations include increase public awareness in reducing the use of plastic but not maximal in Wakatobi, increase tourist visits even not maximal in Tanjung Puting, increase the number of local businesses, and increase public awareness in managing tourist destinations.Keywords: Cooperation, Swiss, Indonesia, “WISATA II”, Sustainable Tourism